Florida Rules for Direct Supervision of Unlicensed Pesticide Applicators - Brett W. Bultemeier; Erin E. Harlow (EDIS, 2021)
In the state of Florida there are three statutory chapters that dictate the rules for pesticide applications. Each chapter, 388 (mosquito), 482 (structural pest control), and 487 (agriculture and other sites), differs on who needs a license to apply pesticides and what the rules are for those who oversee unlicensed applicators. This new 3-page publication will define those rules and give guidance on what is needed to supervise unlicensed applicators in the state of Florida. Written by Brett W. Bultemeier and Erin E. Harlow and published by the UF/IFAS Pesticide Information Office.